The impact of macroeconomic factors on foreign direct investment (FDI) in Malaysia - Rosnah, Mohamad Noor (2018)
The objective of this study is to examine the impact of macroeconomic factors on foreign direct investment (FDI) in Malaysia. There are four independent variables are being investigated to gauge the impact of macroeconomic factors to FDI from the year 2012-2016. The indicators are technology, domestic employment, new market size and international competition. This study is determining the relationship between independent variables and the dependent variable by using Pearson correlation and multiple regression analysis. The findings showed technology, domestic employment and new market size had negative and moderate relationships to the impact on FDI in Malaysia. Meanwhile, the findings of multiple linear regressions show technology, new market size and international competition with significant results. The findings also conclude that domestic employment does show insignificant impact of macroeconomic factors on FDI in Malaysia. For future study, it is recommended that new research to do analysis the relationship between the government policies in promoting and develop FDI in Malaysia.